Cardiac iron load and function in transfused patients treated with deferasirox (the MILE study). (20th September 2016) - Ho, P. Joy; Tay, Lay; Teo, Juliana; Marlton, Paula; Grigg, Andrew; St Pierre, Tim; Brown, Greg; Badcock, Caro‐Anne; Traficante, Robert; Gervasio, Othon L.; Bowden, Donald K.
Abstract: Objectives: To assess the effect of iron chelation therapy with deferasirox on cardiac iron and function in patients with transfusion‐dependent thalassemia major, sickle cell disease (SCD), and myelodysplastic syndromes (MDS). Methods: This phase IV, single‐arm, open‐label study over 53 wk evaluated the change in cardiac and liver iron load with deferasirox (up to 40 mg/kg/d), measured by magnetic resonance imaging (MRI). Results: Cardiac iron load (myocardial T2*) significantly improved ( P = 0.002) overall ( n = 46; n = 36 thalassemia major, n = 4 SCD, n = 6 MDS). Results were significant for patients with normal and moderate baseline cardiac iron ( P = 0.017 and P = 0.015, respectively), but not in the five patients with severe cardiac iron load. Liver iron concentration (LIC) significantly decreased overall [mean LIC 10.4 to 8.2 mg Fe/g dry tissue (dw); P = 0.024], particularly in those with baseline LIC >7 mg Fe/g dw (19.9 to 15.6 mg Fe/g dw; P = 0.002). Furthermore, myocardial T2* significantly increased in patients with LIC <7 mg Fe/g dw, but not in those with a higher LIC. Safety was consistent with previous reports. Conclusions: Once‐daily deferasirox over 1 yr significantly increased myocardial T2* and reduced LIC. This confirms that single‐agent deferasirox is effective in the management of cardiac iron, especially for patients with myocardial T2* >10 ms (Clinicaltrials.gov identifier: NCT00673608).